Age-associated differential microRNA levels in human follicular fluid reveal pathways potentially determining fertility and success of in vitro fertilization. (June 2014) - Diez-Fraile, Araceli; Lammens, Tim; Tilleman, Kelly; Witkowski, Wojciech; Verhasselt, Bruno; De Sutter, Petra; Benoit, Yves; Espeel, Marc; D'Herde, Katharina
Abstract Reproductive life span and fertility have been shown to depend on successful early folliculogenesis, which involves cell-to-cell communication and the concerted regulation of gene expression at both the oocyte and granulosa cell levels. Recently, micro RNAs (miRNAs) were identified as fine-tuners of gene expression. Here, we report that miRNAs can readily be detected within membrane-enclosed vesicles of human follicular fluid. MiRNA expression profiling of the follicular fluid of younger (< 31 years) and older (> 38 years) women revealed a set of four differentially expressed miRNAs. The predicted targets of these miRNAs are clearly enriched in genes involved in heparan-sulfate biosynthesis, extracellular matrix–receptor interaction, carbohydrate digestion and absorption, p53 signaling, and cytokine–cytokine-receptor interaction. Several of these pathways have been reported to be determinants of fertility, suggesting that this set of miRNAs and their respective targets should be evaluated in relation to reproductive aging and assisted reproduction.